One thousand soils for molecular understanding of belowground carbon cycling - Bowman, Maggie M.; Heath, Alexis E.; Varga, Tamas; Battu, Anil K.; Chu, Rosalie K.; Toyoda, Jason; Cheeke, Tanya E.; Porter, Stephanie S.; Moffett, Kevan B.; LeTendre, Brittany; Qafoku, Odeta; Bargar, John R.; et al. (Frontiers in Soil Science, 2023)
While significant progress has been made in understanding global carbon (C) cycling, the mechanisms regulating belowground C fluxes and storage are still uncertain. New molecular technologies have the power to elucidate these processes, yet no widespread standardized implementation of molecular techniques. To address this gap, we introduce the Molecular Observation Network (MONet), a decadal vision from the Environmental Molecular Sciences Laboratory (EMSL), to develop a national network for understanding the molecular composition, physical structure, hydraulic and biological properties of soil and water. These data are essential for advancing the next generation of multiscale Earth systems models. In this paper, we discuss the 1000 Soils Pilot for MONet, including a description of standardized sampling materials, protocols, and a use case to highlight the utility of molecular-level and microstructural measurements for assessing the impacts of wildfire on soil. While the 1000 Soils Pilot generated a plethora of data, we focus on assessments of soil organic matter (SOM) chemistry via Fourier-transform ion cyclotron resonance-mass spectrometry and microstructural properties via X-ray Computed Tomography to highlight the effects of recent fire history in forested ecosystems on belowground C cycling. We observed decreases in soil respiration, microbial biomass, and potential enzyme activity in soils with high frequency burns. Additionally, the nominal oxidation state of carbon in SOM increased with burn frequency in surface soils. This results in quantifiable shifts in the molecular signature of SOM, shows that wildfire may result in oxidation of SOM, and structural changes to soil pore networks that persist into deeper soils.